2021
DOI: 10.1186/s12872-021-02319-5
|View full text |Cite
|
Sign up to set email alerts
|

Human epididymis protein 4: a novel predictor of ischemic cardiomyopathy

Abstract: Background The prognostic value of human epididymis protein 4 (HE4) in patients with ischemic cardiomyopathy (ICM) is unknown. Methods A total of 103 patients with ICM were prospectively enrolled in this study from Hunan Provincial People’s Hospital between February 2019 and June 2019. All patients were tested for HE4 levels at baseline and follow-up. Endpoints of the study included cardiovascular death and heart failure-related hospitalization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Our results further showed that the ability of HE4 to predict HF after ACS is surprising and promising. Although some studies [41] have shown that renal function deteriorates with increasing levels of HE4 and other studies [42][43][44][45] showed a correlation between HE4 and Cr, our study clarified the independent influence of HE4 after adjusting for confounding factors. Therefore, we believe that HE4 has a potential predictive value and may guide better management of the onset of HF after ACS among women.…”
Section: Discussioncontrasting
confidence: 57%
“…Our results further showed that the ability of HE4 to predict HF after ACS is surprising and promising. Although some studies [41] have shown that renal function deteriorates with increasing levels of HE4 and other studies [42][43][44][45] showed a correlation between HE4 and Cr, our study clarified the independent influence of HE4 after adjusting for confounding factors. Therefore, we believe that HE4 has a potential predictive value and may guide better management of the onset of HF after ACS among women.…”
Section: Discussioncontrasting
confidence: 57%
“…Approximately 46% of heart failure patients presented slight increases in HE4, of the order of 300 pmol/L, and this protein was identified as a biomarker of myocardial fibrosis [162]. In patients with effusions, 35% may exhibit HE4 values that are three times above the cut-off point, with levels reaching up to 450 pmol/L [95,160].…”
Section: Human Epididymis Protein 4 (He4)mentioning
confidence: 99%
“… 9 Our previous research findings demonstrated that HE4 could predict the prognosis in patients with ischemic cardiomyopathy and idiopathic pulmonary hypertension with right heart failure. 10 , 11 In 2013, de Boer et al 12 found that HE4 levels could predict the poor prognosis in patients with AHF. Arnold Piek et al 13 also found that HE4 are associated with heart failure severity in patient with chronic heart failure.…”
Section: Introductionmentioning
confidence: 99%